Absence of Obesity Paradox in All-Cause Mortality Among Chinese Patients With an Implantable Cardioverter Defibrillator: A Multicenter Cohort Study - Zhou, Bin; Sun, Xuerong; Yu, Na; Zhao, Shuang; Chen, Keping; Hua, Wei; Su, Yangang; Yang, Jiefu; Liang, Zhaoguang; Xu, Wei; Tang, Min; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2021)
Background: The results of studies on the obesity paradox in all-cause mortality are inconsistent in patients equipped with an implantable cardioverter-defibrillator (ICD). And there is a lack of relevant studies on Chinese populations with a large sample size. This study aimed to investigate whether the obesity paradox in all-cause mortality is present among the Chinese population with an ICD. Methods: We conducted a retrospective analysis of multicenter data from the SUMMIT registry (Study of Home Monitoring System Safety and Efﬁcacy in Cardiac Implantable Electronic Device–implanted Patients) in China. The outcome was all-cause mortality. Kaplan-Meier curves, Cox proportional hazards models, and smooth curve fitting were used to investigate the association between body mass index (BMI) and all-cause mortality. Results: After inclusion and exclusion criteria, 970 patients with an ICD were enrolled. After a median follow-up of 5.0 years (interquartile, 4.1-6.0 years), 213 (22.0%) patients occurred all-cause mortality. According to Kaplan-Meier curves and multivariate Cox proportional hazards models, BMI had no significant impact on all-cause mortality, whether as a continuous variable or a categorical variable classified by various BMI categorization criteria. The fully adjusted smoothed curve fit showed a linear relationship between BMI and all-cause mortality (p-value of 0.14 for the non-linearity test), with the curve showing no statistically significant association between BMI and all-cause mortality (per 1 kg/m2 increase in BMI, Hazard ratio 0.97, 95% confidence interval 0.93-1.02, p = 0.2644). Conclusions: The obesity paradox in all-cause mortality was absent in Chinese patients with an ICD. Prospective studies are needed to further explore this phenomenon.